2021
DOI: 10.3389/fmicb.2021.664353
|View full text |Cite
|
Sign up to set email alerts
|

RIPK3-Dependent Necroptosis Limits PRV Replication in PK-15 Cells

Abstract: Pigs infected by pseudorabies virus (PRV) display necrotic pathology in multiple organs. The mechanism by which PRV induces cell death is still unclear. Recently, necroptosis was identified as a programmed process dependent on the receptor interacting protein kinase 3 (RIPK3) and mixed lineage kinase-like protein (MLKL). In this study, we demonstrated that PRV induced RIPK3-dependent necroptosis in PK-15 cells. The data showed that PRV infection caused cell death with Propidium Iodide (PI)-positive staining. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In this study, calcein-AM/PI staining and TUNEL staining were used to examine necroptosis and apoptosis in ARPE19 cells, respectively. PI only penetrates damaged cell membranes and releases red fluorescence when embedded in double-stranded DNA, so it has been used to identify necroptotic cells in recent studies [ 37 , 38 ]. TUNEL is a commonly used method to label apoptotic cells by specifically detecting DNA breaks that occur during apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, calcein-AM/PI staining and TUNEL staining were used to examine necroptosis and apoptosis in ARPE19 cells, respectively. PI only penetrates damaged cell membranes and releases red fluorescence when embedded in double-stranded DNA, so it has been used to identify necroptotic cells in recent studies [ 37 , 38 ]. TUNEL is a commonly used method to label apoptotic cells by specifically detecting DNA breaks that occur during apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Receptor-interacting protein kinases (PIPKs), i.e., RIP kinases, are a family of serine/threonine kinases that play a wide variety of functional roles in cellular signaling during pathogen infection. Several RIPKs are involved in necroptosis, which is a form of inflammatory programmed cell death that plays a role in fighting viral infections [ 124 ]. Necroptosis leads to cell membrane rupture and leakage of cellular contents [ 125 ], thus initiating inflammation and adaptive immunity against viruses [ 126 ].…”
Section: The Most Frequently Targeted Kinases For Antiviral Drug Deve...mentioning
confidence: 99%
“…Necroptosis also limits Vaccinia virus replication, and RIPK3 deletion in mice caused an increase in virus replication [ 135 ]. Furthermore, a study involving the use of swine kidney cell line (PK-15) and pseudorabies virus (PRV) [ 124 ] reported the induction of necroptosis by PRV via the RIPK3 pathway. Although PRV has induced necroptosis via the RIPK3 pathway in PK-15 cells, the study has shown that RIPK3 and MLKL knockdown had reduced necroptosis and enhanced PRV replication [ 124 ].…”
Section: The Most Frequently Targeted Kinases For Antiviral Drug Deve...mentioning
confidence: 99%
See 1 more Smart Citation
“…As an epidemic swine pathogen, pseudorabies virus (PRV) causes significant economic losses to the global swine industry and is characterized by acute and high fever and neurological symptoms in piglets, abortions and stillbirths in sows, and digestive system diseases, such as vomiting, diarrhea, necrotizing enteritis, in adult pigs ( 7 ). Pseudorabies (PR) caused by PRV is a serious infectious disease, with mortality of nearly 100% in piglets ( 8 ). The swine is the natural host for PRV, and the virus can also infect most mammals, including cattle, rodents, and dogs ( 9 ).…”
Section: Introductionmentioning
confidence: 99%